COVID-19 pandemic impact on the therapeutic setting in Mental Health Services - Trabucco, Alice; Aguglia, Andrea; Amerio, Andrea; Corsini, Giovanni; Cervetti, Alice; Escelsior, Andrea; Costanza, Alessandra; Serafini, Gianluca; Amore, Mario (Acta Biomedica Atenei Parmensis, 2021)
Background: The new 2019 coronavirus disease (COVID-19) outbreak forced mental health providers to overcome their general reluctance about telematic assistance, shifting from a face-to-face approach to online therapy to promote continuity of care for psychiatric patients. Methods: An ad-hoc web-based survey questionnaire assessing the impact of the COVID-19 pandemic on therapeutic setting in Mental Health Services was sent via email from March 15, 2021 to June 15, 2021 to mental health providers in Genova, Italy. The survey was anonymous and a free Google Forms® software was used. Results: Two hundred nineteen mental health providers completed the survey, and the overall response rate (ORR) was 65%. During the COVID-19 pandemic period, the continuity of care was mainly guaranteed using electronic devices. Psychologists reported a higher availability of video call assistance service to guarantee continuity of care for psychiatric patients compared to psychiatrists and psychotherapists (p<0,001). Psychiatrists reported the lowest degree of satisfaction about this new telematic approach (p<0,01), while psychologists and to a lesser extent psychotherapists speculated to use it even in non-pandemic times (p=0,02). Conclusions: COVID-19 pandemic creates an opportunity to overcome normative, technological and cultural barriers to the use of online psychotherapy, showing the importance of adapting the therapeutic setting to both collective and individual needs. Despite initial concerns about its effectiveness and efficacy, a general degree of satisfaction was expressed by the majority of the mental health providers. Further efforts will be needed to enhance this new way of working and to train therapists with particular regard to those employed in the public health system.